Psychological aspects of visual advertising - Terelak, Jan Felicjan (Studia Psychologica: Theoria et praxis, 2004)
This paper has a pictorial character of contemporary psychological knowledge needed to create effective visual advertising. In the first part the author underlines the persuasional aspects of advertising, focusing on changing personal attitude from neutral to positive. Second part describes psychological mechanisms of visual perception and its quantitative aspects. The paper is finished with practical conclusion addressed to creators of visual advertising.